An Analysis of Students’ Ability In Writing Invitation Letters at Second Grade of SMKN 6 Padang - Widya Juli Astria; Sherly Franchisca; Lailatul Husna; Wahyu Permata Ningsih (Journal on Education, 2023)
The objective of this research was to find out the students' abilities and students' difficulties in writing invitation letters. This research was conducted at SMKN 6 Padang in the 2021/2022 academic year. This research was taken based on the fact that most of the students could not write English well, especially in writing invitation letters. Researchers want to analyze the ability of students in writing invitation letters in class II SMKN 6 Padang. This research was conducted in class II SMKN 6 Padang. Sources of data in this study were students of class II TKJ 1 SMKN 6 Padang. This research is a descriptive study using quantitative methods. Test data collection instruments, data analysis techniques; data classification, checking data validity, calculating results (values), and data descriptions. The population is 64 students of SMKN 6 Padang, namely two TKJ one and two PH three culinary two. The sample consists of 34 students. Based on the results of the tests given, the researchers found that the students' ability to write invitation letters for class II SMKN 6 Padang was in the high category (76.91%), (1) The students' ability to write heading invitation letters was sufficient (44.11%). (2) The students' ability to write salutation in invitation letters is high (73.52%). (3) The students' ability to write the body in invitation letters is very high (100%). (4) The students' ability to write closing invitation letters is high (61.76%). (5) The students' ability to write signatures is high (88.23%). Based on the results of student tests, the researcher stated that the difficulty in writing invitation letters was due to a lack of vocabulary.